Green management training program and its effect on staff nurses’ organizational citizenship behavior - Nada Salah Yassin; Dalal Talaat Akel; Hanaa Mohamed Abd Rabou (BMC Nursing)
Abstract Background Green management practices are essential for organizational sustainability, and their adoption in hospitals can help reduce environmental impact. Organizational citizenship behavior further enhances green management efforts. Aim of the study This study aimed to assess the effect of a green management training program on staff nurses’ organizational citizenship behavior. Design Quasi-experimental design with a pretest-posttest approach. Setting This study was carried out in Al-Ahrar Teaching. Subjects 85 staff nurses participated in the study. Tools of data collection green management knowledge questionnaire, employee green behaviors scale, and organizational citizenship behavior scale were used for data collection. Result Significant improvements were observed in staff nurses’ knowledge of green management (16.5–89.4%), employee green behavior (5.9–64.7%), and organizational citizenship behavior (7.1–70.6%) at pre- and post- phases respectively. Conclusion The green management training program effectively improved organizational citizenship behavior, supporting the research hypothesis. Trial registration number Not applicable. Clinical trial number Not applicable.